Preliminary study on formulation of goat milk with freeze dried fruit potentianally for pregnant women - Salleh, Nunshaimah; Yaacob, Yanti; Ali, Rosliza; Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina (2024)
A preliminary study on potential formulation of goat milk with freeze-dried fruits for pregnant women is the study to explore the formulation which can remove or to lessen the ‘goaty taste’ of the goat milk itself. Goat milk’s nutritional advantages, including digestibility and unique fatty acids compositions complement the benefits of freeze-dried fruit which retain essential nutrients and flavours; hence, it will enhance the nutrition of the formulation. The optimal ratio for goat's milk formulation is 6:4, comprising 6g of goat's milk and 4g of dried fruit. Following several testing and modifications to eliminate the ‘goaty taste’ and enhance the overall taste, the optimal formulation of goat milk is 6:2:0.5:0.5:1, corresponding to goat milk powder, honeydew, dragon fruit, avocado, and natural honey, respectively.